2015
DOI: 10.1108/h-07-2013-0049
|View full text |Cite
|
Sign up to set email alerts
|

Accountability through accounting and reporting lenses

Abstract: Purpose – The purpose of this paper is to review, understand and document the contemporary waqf-S management, financial accounting and reporting practices and to understand relevant drivers behind the current accountability culture in waqf-S, aiming at exploring the intertwined nature of accounting, reporting and the religion of Islam. The accountability literature has been relatively scant on the role played by accounting and reporting in not-for-profit, religious-based organizations and its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Stakeholder theory offers a more inclusive accountability perspective that recognizes the need for Islamic non-profit entities to be accountable to multiple stakeholders (Meutia et al, 2010). This is important in order to prevent abuse by management (Yaacob et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stakeholder theory offers a more inclusive accountability perspective that recognizes the need for Islamic non-profit entities to be accountable to multiple stakeholders (Meutia et al, 2010). This is important in order to prevent abuse by management (Yaacob et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on accounting for waqf institutions and bodies in Malaysia have focused on the reporting and accountability of waqf organisations (Ihsan, 2007;Ihsan & Adnan, 2009;Nahar & Yaacob, 2011;Tohirin & Hudayati, 2011;Masruki & Shafii, 2013;Yaacob et al, 2015), waqf management and governance (Iqmal et al, 2018;Chowdhury, 2011;Kamri, 2010) and the reason why there is a lack in waqf reporting (Daud, 2018). However, this current research provides insights and focuses on the areas not covered by previous research, that is to understand how the management of waqf institutions practice their accounting in adhering to a non-specific prevailing accounting standard whilst conforming to waqf principles.…”
Section: Accounting For Non-profit Contextmentioning
confidence: 99%
“…On the other hand, the effectiveness of Waqf is also related to the idea of accountability (Arshad & Zain, 2017;Mansor & Jamil, 2018). As reported by Noordin et al (2017); Siswantoro, Rosdiana, and Fathurahman (2017); Yaacob, Petra, and Sumardi (2015), accountability is highly discussed and highlighted among scholars in ensuring that Waqf institutions are operated based on integrity and trust (Yaacob et al, 2015). Furthermore, the report by audit department showed that management of Waqf property in Peninsular Malaysia is still not satisfied, leading to the increase in queries and doubts the effectiveness and efficiency of this institution in handling Waqf properties (Jabatan Audit Negara, 2017).…”
Section: Empirical Study and Indicators Of Effectiveness In Waqf Institutionmentioning
confidence: 99%